Effect of mechanical cycling on the flexural strength of densely sintered ceramics - Itinoche, Koiti Marco; Ozcan, Mudu; Bottino, Marco Antonio; Oyafuso, Denise (Elsevier B.V., 2006)
Objectives. The aim of this study was to evaluate the effect of mechanical cycling on the biaxial flexural strength of two densely sintered ceramic materials.Methods. Disc shaped zirconia (In-Ceram Zirconia) and high alumina (Procera AllCeram) ceramic specimens (diameter: 15 min and thickness: 1.2 mm) were fabricated according to the manufacturers' instructions. The specimens from each ceramic material (N = 40, n = 10/per group) were tested for flexural strength either with or without being subjected to mechanical cycling (20,000 cycles under 50 N load, immersion in distilled water at 37 degrees C) in a universal testing machine (1 mm/min). Data were statistically analyzed using two-way ANOVA and Tukey's test (alpha = 0.05).Results. High alumina ceramic specimens revealed significantly higher flexural strength values without and with mechanical cycling (647 +/- 48 and 630 +/- 143 MPa, respectively) than those of zirconia ceramic (497 +/- 35 and 458 +/- 53 MPa, respectively) (p < 0.05). Mechanical cycling for 20,000 times under 50 N decreased the flexural strength values for both high alumina andSignificance. High alumina ceramic revealed significantly higher mean flexural strength values than that of zirconia ceramic tested in this study either with or without mechanical cycling conditions. (C) 2005 Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
Keywords: alumina; ceramics; flexural strength; in-ceram; mechanical cycling; Procera; zirconia